2009
DOI: 10.1111/j.1600-6143.2009.02793.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant Therapy Adherence and Graft Failure Among Pediatric Renal Transplant Recipients

Abstract: The study objective was to determine the association between immunosuppressant therapy (IST) adherence and graft failure among pediatric renal transplant recipients (RTRs) using data reported in the United States Renal Data System (USRDS), which contains Medicare prescription claims. RTRs (≤18 years) who received their only transplant during 1995-2000, experienced graft survival more than 6 months posttransplant, had 36 months of USRDS data (or had data until graft failure or death), utilized Medicare IST cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 51 publications
1
74
1
1
Order By: Relevance
“…Pinsky et al 1 and Chisholm et al 2 confirmed that decreased adherence to therapy is associated with an increased risk of graft failure 1,2 and death, 1 and with increased health-care costs. 1 specifically, Pinsky et al 1 found that patients in the least adherent and secondleast adherent quartile were at 80% and 63% higher risk of graft failure than patients in the highest quartile, respectively.…”
Section: Transplantationmentioning
confidence: 92%
See 2 more Smart Citations
“…Pinsky et al 1 and Chisholm et al 2 confirmed that decreased adherence to therapy is associated with an increased risk of graft failure 1,2 and death, 1 and with increased health-care costs. 1 specifically, Pinsky et al 1 found that patients in the least adherent and secondleast adherent quartile were at 80% and 63% higher risk of graft failure than patients in the highest quartile, respectively.…”
Section: Transplantationmentioning
confidence: 92%
“…two reports on kidney transplantation, one in adults 1 and one in children (18 years of age or younger), 2 demonstrate the adverse impact of drug non adherence on both clinical 1,2 and economic outcomes. 1 Both the studies by Pinsky et al 1 and Chisholm et al 2 used more sophisticated methodologies than those employed by previous studies, and both included large numbers of patients (n = 15,525 1 and n = 877 2 , respectively), which enhanced their statistical power. Both used sizeable multicenter databases (the medicare prescription refill claims database and the united states renal Data system 1,2 ), which enhanced the generalizability of results, and both assessed adherence to immunosuppression therapy as a continuous parameter in patients on different immunosuppressive regimens.…”
Section: Transplantationmentioning
confidence: 96%
See 1 more Smart Citation
“…Les causes d'échecs précoces sont principalement les thromboses vasculaires et la récidive de la maladie initiale [25]. À long terme la néphropathie chronique d'allogreffe est la première cause de perte du greffon ; outre les facteurs immunologiques, phénomènes d'ischémie-reperfusion, toxicité médicamen-teuse des anticalcineurines, on observe une part croissante de la non observance thérapeutique dans son apparition [29]. Ce problème majeur est observé principalement chez les jeunes adolescents exprimant ainsi leur souffrance face à la maladie chronique.…”
Section: Causes D'échecunclassified
“…However, we now understand that nonadherence is a significant concern in transplantation and data from the United States Renal Data System have confirmed that it is, indeed, a risk factor for poor graft survival. 32 In order to improve outcomes for our patients, the initial conditions of the transplanted graft need to be assessed, as these have an impact on its long-term survival. Nankivell et al 33 demonstrated that subclinical inflammation posttransplant is a risk factor for progression of chronic interstitial damage.…”
Section: The Kidney Graft Journey and Risk Managementmentioning
confidence: 99%